Construct validity of Minnesota Multiphasic Personality Inventory‐2‐Restructured Form scale scores in correctional settings. (24th March 2020) - Tylicki, Jessica L.; Phillips, Tasha R.; Ben‐Porath, Yossef S.; Sellbom, Martin
Abstract: Limited research has examined the link between Minnesota Multiphasic Personality Inventory‐2‐Restructured Form (MMPI‐2‐RF) scales and contemporary personality and psychopathology models within correctional settings. This study focused on establishing construct validity of the MMPI‐2‐RF in offender samples from a broad personality framework. Two samples of incarcerated men and women completed a battery of broadband personality measures and narrowband measures that capture conceptually related constructs. To examine how MMPI‐2‐RF scale scores and criterion measures converged in a conjoint latent structure, we conducted a series of exploratory structural equation modelling analyses, which revealed factors similar to those of extant hierarchical personality models. At the broadband level, four factors (Positive Activation, Negative Affectivity, Inhibition and Agreeableness) were observed, whereas narrowband criteria yielded five factors (Behavioural Approach System, Disinhibition/Externalizing, Danger/Thrill Seeking, Self‐Assurance/Boldness, and Unemotionality/Coldheartedness). MMPI‐2‐RF scale scores converged with the personality/psychopathology models in a theoretically expected manner. Limitations and directions for future research are discussed. © 2020 John Wiley & Sons, Ltd.